2004
DOI: 10.1080/13576500444000065
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Social Disclosure on the Intensity of Affect Provoked by Autobiographical Memories

Abstract: Affect associated with negative autobiographical memories fades faster over time than affect associated with positive autobiographical memories (the fading affect bias). Data described in the present article suggest that this bias is observed when people use their own words to describe both the emotions that they originally felt in response to events in their lives and the emotions that they feel when they recall those events. The data also suggest that the fading affect bias is not a consequence of distortion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
115
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(132 citation statements)
references
References 22 publications
(46 reference statements)
16
115
1
Order By: Relevance
“…They found that the memories of traumatic events were more reliable and consistent over time than were the memories of positive events. However, they also found that the overall memory quality and vividness of the positive events declined more over time than did those of the negative memories, which seems contrary to the fading affect bias reported in other studies (e.g., Holmes, 1970;Skowronski et al, 2004;Walker et al, 2003;Walker et al, 1997). Levine and Bluck (2004) asked students who were either happy or unhappy about the O. J. Simpson verdict how clearly they recalled the news event 2 months, as well as 1 year, after the event had occurred.…”
contrasting
confidence: 52%
See 1 more Smart Citation
“…They found that the memories of traumatic events were more reliable and consistent over time than were the memories of positive events. However, they also found that the overall memory quality and vividness of the positive events declined more over time than did those of the negative memories, which seems contrary to the fading affect bias reported in other studies (e.g., Holmes, 1970;Skowronski et al, 2004;Walker et al, 2003;Walker et al, 1997). Levine and Bluck (2004) asked students who were either happy or unhappy about the O. J. Simpson verdict how clearly they recalled the news event 2 months, as well as 1 year, after the event had occurred.…”
contrasting
confidence: 52%
“…Skowronski, Gibbons, Vogl, and Walker (2004) found the fading affect bias to be related to the rehearsal of an event.…”
mentioning
confidence: 99%
“…Kahneman et al, 1982;Sedikedes et al, 2003;Skowronski et al, 1991Skowronski et al, , 2004Walker et al, 2003), might be another reason for investigators' inaccurately rating themselves, allowing them to obviate exercising the required cognitive effort when self-rating. To lessen such concerns, the researchers advised the investigators to examine the videorecording of the interview which they were to self-assess at least twice before entering their scores.…”
Section: Discussionmentioning
confidence: 99%
“…One reason might be that individuals, when reflecting, find it more demanding to prompt negative self-inferences than negative other-inferences since they invariably possess more positive knowledge about themselves than about others (Kihlström, Beer, & Klein, 2003;Prentice, 1990). Moreover, these positive recollections decay at a slower rate than their less favourable counterparts (Skowronski, Gibbons, Vogl, & Walker, 2004;Walker et al, 2003). As such, positive information is elevated (or reconstructed as positive) in one's hierarchy of memory, and self-threatening feedback is derogated (Baumeister, Campbell, Krueger, & Vohs, 2003;Sedikides, Gaertner, & Toguchi, 2003), leaving heuristically driven information to result in biased judgments (Kahneman, Slovic, & Tversky, 1982).…”
Section: Self-evaluation As a Taskmentioning
confidence: 99%
“…Of course, this immediately raises the question to a self-enhancement adherent as to why positively-biased memories are so readily available; indeed, as diary studies have demonstrated, people remember positive life events better than negative life events (Skowronski, Betz, Thompson, & Shannon, 1991;Walker, Skowronski, & Thompson, 2003), and, relatedly, affect associated with positive life events dissipates at a slower rate than affect associated with negative life events (Skowronski, Gibbons, Vogl, & Walker, 2004;Walker et al, 2003) . It seems plausible to assume that the desire to view oneself favourably could result in positive information receiving a privileged place in memory.…”
Section: Addressing Alternative Explanationsmentioning
confidence: 99%